Paricalcitol For CKD-MBD Associated With Secondary Hyperparathyroidism: A Case Series Focus On TRAP5b, b-ALP, and DKK-1 - Suprapti, Budi; Hartono, Frenky; Iqbal, Muhammad; Zuhri, Muhammad Isnaini; Aditiawardana, Aditiawardana (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
Chronic kidney disease (CKD) lead to secondary hyperparathyroidism (sHPT) that caused by phosphate retention and hypocalcemia. This condition known as mineral and bone disorder (CKD-MBD). The increase in parathyroid hormone would increase bone turnover that result in an increased risk of bone fractures, and vascular calcification. These will increase the levels of tartrate-resistant acid phosphatase 5b (TRAP5b), and bone-specific alkaline phosphatase (b-ALP), which is a marker of bone turnover, and also dickkopf-related protein 1 (DKK-1), which is an inhibitor of the Wnt pathway. Secondary hyperparathyroidism in CKD also caused by calcitriol deficiency. Paricalcitol is a synthetic calcitrol analogue used to reduce parathyroid hormone (iPTH) with minimal calcemic and phosphatemic activity. Vitamin D receptor activation by paricalcitol will decrease TRAP5b, b-ALP, and DKK-1. In this study we reported 9 cases of CKD-MBD with Hemodialysis (HD) and associated with sHPT. Four of nine cases received 5μg paricalcitol every HD (twice a week) while the others five is not. Level of iPTH, phosphate, calcium, TRAP5b, b-ALP, and DKK-1 were measured before initiation of study and after three months treatment. According to this study, the paricalcol administration suppresses the increase in iPTH level, bone turnover and vascular calcification showed by decreasing or supresses the increase b-ALP, TRAP5b, DKK-1 leves without increasing calcium and phosphate levels.